2016
DOI: 10.1111/1468-0009.12196
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Economic Evaluation to Inform Newborn Screening Policy Decisions: The Washington State Experience

Abstract: Policy Points:r Newborn screening not only saves lives but can also yield net societal economic benefit, in addition to benefits such as improved quality of life to affected individuals and families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 74 publications
0
24
0
3
Order By: Relevance
“…We believe our study provides a useful and timely economic assessment that can inform decisions on the adoption of the federally recommended SCID screen in state NBS programs. The CBA conducted in Washington 26 was a crucial step in the process of approving the adoption of SCID in that state, 59 and earlier versions of the model have been shared with other states.…”
Section: Discussionmentioning
confidence: 99%
“…We believe our study provides a useful and timely economic assessment that can inform decisions on the adoption of the federally recommended SCID screen in state NBS programs. The CBA conducted in Washington 26 was a crucial step in the process of approving the adoption of SCID in that state, 59 and earlier versions of the model have been shared with other states.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness is not commonly used as a criterion for policy decisions in public health in the United States [ 68 ]. That is true specifically for newborn screening policies [ 69 ], with a few exceptions [ 70 ]. It should also be noted that most policy decisions for other types of newborn screening in European countries likewise have not been informed by cost-effectiveness analyses, although screening costs are often considered [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both local and international studies have shown the cost-efficiencies gained by adopting MS/MS technology for expanded newborn screening. [24][25][26] The available evidence is sufficient for policymakers to consider implementing a universal expanded screening programme in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%